PERSPEKTIF VALUES EDUCATION DALAM KAJIAN FILSAFAT PENDIDIKAN BERBASIS 3N (NALAR, NURANI, DAN NALURI) - I Putu Suardipa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Values provided by Living Values Education (LVE) is the value of the process ofcharacter education that is done with various methods and approaches so as to create qualified human resources based on academic and religious the best solution in instilling values through educators and learners in cooperation in achieving the educational goals of Indonesia. LVE in the context of education focuses on humanized learning through 3N (Nalar, Nuranar, and Naluri) which is strong and characteristic. The context of reasoning is that humans can determine moral, ethical and aesthetic values. Conscience is the application of moral consciousness that grows and develops in the human heart in concrete situations. Instinct or instinct is a pattern of behavior and reaction to a certain stimulus. Instinct in the context of learning more focused on the abilityof teachers to make teachers have a motherly instinct or fatherly instinct. In this role, the teacher must make the learning process of “humanization” (humanizing human) learning based on love, teasing and foster forming the atmosphere of principled in kinship, kindness, empathy, love and appreciation toward others. Through this learning education will greatly help students / learners to personality independent, healthy physical, healthy mental, smart, and become an ideal member of society.